Oxidation and Acetylation of Ursolic and Oleanolic Acids Isolated from Fragraea fragrans fruits; Antiproliferation of P388 Leukemia Cells - Dasril Basir; Julinar Julinar; Eva Agustriana; Budi Untari (Universitas Gadjah Mada, 2014)
An interesting natural product chemistry aspect of Fragraea fragrans is that their fruits are richness with ursolic acid and its isomer oleanolic acid (3.05% of dried powder). As our continuous work on these inseparable structural isomeric triterpenes, this paper reports that 51.0% of inseparable 3-oxo-ursolic[3-oxo-oleanolic] acids and 48.6% of inseparable 3-acethyl-ursolic [3-acethyl-oleanolic] acids have already been made from those triterpenes as starting materials of the oxidized and acetylated compounds and evaluated their activity against P388 leukemia cells. The activity of 3-oxo-ursolic [3-oxo-oleanolic] acids with IC50 = 18.6 µg/mL exhibited three-fold more potent against P388 leukemia cell proliferations compared to ursolic [oleanolic] acids with IC50 = 53.5 µg/mL; while the 3-acethyl-ursolic [3-acethyl-oleanolic] acids with IC50 = 37.9 µg/mL showed two-fold more potent then their parent triterpenes (IC50 = 53.5 µg/mL) in the inhibition of P388 leukemia cell growth.